Geomagnetic Induced Current Analysis in A Hybrid PV Power System Network - Johan F.N.; Ab Aziz N.F.; Khurshid Z.M.; Yasin Z.M.; Salim N.A. (Institute of Electrical and Electronics Engineers Inc., 2023)
DC transformers; Geomagnetism; Intercalation; Wind power; Current analysis; Earth's surface; Geomagnetic disturbance; Geomagnetic induced currents; Geomagnetic storm; Half cycle; Photovoltaics; Power absorption; Power system networks; PV power systems; Hybrid systems